2016
DOI: 10.1177/1060028016653139
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacist-Provided Medication Management in Interdisciplinary Transitions in a Community Hospital (PMIT)

Abstract: This study provides new information from previous studies and represents the largest study with significant and sustained reductions in re-presentations. Integrating a pharmacist into an interdisciplinary team for medication management during TOC in a community health system is beneficial for patients and financially favorable for the institution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(41 citation statements)
references
References 27 publications
1
40
0
Order By: Relevance
“…A systematic review investigating economic evaluations of clinical pharmacist interventions found an overall positive impact on hospital budgets; however, the quality of the included studies was limited . The studies in this review mostly found a positive effect on cost using methods such as reduced costs from readmissions and bed‐days where the cost of the time for the pharmacist‐led intervention was subtracted. Only one study performed a robust cost‐effectiveness analysis, which did not find a significant effect .…”
Section: Discussionmentioning
confidence: 94%
See 4 more Smart Citations
“…A systematic review investigating economic evaluations of clinical pharmacist interventions found an overall positive impact on hospital budgets; however, the quality of the included studies was limited . The studies in this review mostly found a positive effect on cost using methods such as reduced costs from readmissions and bed‐days where the cost of the time for the pharmacist‐led intervention was subtracted. Only one study performed a robust cost‐effectiveness analysis, which did not find a significant effect .…”
Section: Discussionmentioning
confidence: 94%
“…. In total, 11,896 publications were imported, 544 full texts were read, and 28 publications were included in the analysis.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations